2022
DOI: 10.5334/aogh.3465
|View full text |Cite
|
Sign up to set email alerts
|

Household Air Pollution and Respiratory Symptoms a Month Before and During the Stringent COVID-19 Lockdown Levels 5 and 4 in South Africa

Abstract: Background: Household air pollution (HAP) is associated with adverse human health impacts. During COVID-19 Lockdown Levels 5 and 4 (the most stringent levels), South Africans remained at home, potentially increasing their exposure to HAP. Objectives:To investigate changes in fuel use behaviours/patterns of use affecting HAP exposure and associated HAP-related respiratory health outcomes during COVID-19 Lockdown Levels 5 and 4.Methods: This was a cross-sectional online and telephonic survey of participants from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Dherani et al (2022) found that exposure to higher concentrations of PM 2.5 from cooking-derived smoke pollution is associated with an increased prevalence of pneumonia infection in young children. Wright et al (2022) reported on increased exposure to HAP and respiratory illness during COVID-19 lockdown levels 5 and 4 in South Africa as people switched to 'dirty fuels'. Nuhu, Bukari and Banye (2022) revealed that LPG, followed by charcoal-improved cookstoves (ICS), offers major health benefits.…”
Section: Health Effectsmentioning
confidence: 99%
“…Dherani et al (2022) found that exposure to higher concentrations of PM 2.5 from cooking-derived smoke pollution is associated with an increased prevalence of pneumonia infection in young children. Wright et al (2022) reported on increased exposure to HAP and respiratory illness during COVID-19 lockdown levels 5 and 4 in South Africa as people switched to 'dirty fuels'. Nuhu, Bukari and Banye (2022) revealed that LPG, followed by charcoal-improved cookstoves (ICS), offers major health benefits.…”
Section: Health Effectsmentioning
confidence: 99%
“…With people spending majority of their time in their dwellings, their exposure to household air pollution (HAP) became reason for concern; especially among people who rely on so-called 'dirty fuels' as their main source of energy for cooking and / or heating. A recently published study by Wright et al (2022) conducted a retrospective online / telephonic survey to investigate fuel use behaviours / patterns of use affecting HAP exposure and associated HAP-related respiratory health outcomes a month before and during Lockdown Levels 5 and 4, i.e., the two most stringent levels. Participants were drawn from an existing market research company panel (since field campaigns were not possible) from Gauteng, Western Cape, KwaZulu-Natal and Eastern Cape where COVID-19 cases were highest at the time of study planning.…”
Section: Research Brief Household Air Pollution and Respiratory Sympt...mentioning
confidence: 99%